Neurocognitive Performance Stability in a Multiplex Multigenerational Study of Schizophrenia - Roalf, David R. (Oxford University Press, 2013)
Certain cognitive measures are heritable and differentiate individuals at risk for schizophrenia from unaffected family members and healthy comparison subjects. These deficits in neurocognitive performance in patients with schizophrenia appear stable in the short-term. However, the duration of most, but not all, longitudinal studies is modest and the majority have relied on traditional average performance measures to examine stability. Using a computerized neurocognitive battery (CNB), we assessed mean performance (accuracy and speed) and intra-individual variability (IIV) in a longitudinal study aimed to examine neurocognitive stability in European-American multiplex families with schizophrenia. Thirty-four patients with schizophrenia, 65 unaffected relatives, and 45 healthy comparison subjects completed the same computerized neurocognitive assessment over approximately 5 years. Measures of mean performance showed that patients had stable accuracy performance but were slower in many neurocognitive domains over time as compared with unaffected family members and healthy subjects. Furthermore, patients and family members showed dissociable patterns of change in IIV for speed across cognitive domains: compared with controls, patients showed higher across-task IIV in performance compared with family members, who showed lower across-task IIV. Patients showed an increase in IIV over time, whereas family members showed a decrease. These findings suggest that measures of mean performance and IIV of speed during a CNB may provide useful information about the genetic susceptibility in schizophrenia.